Murabaha Contract Dispute Resolution Procedure - Rezki Akbar Norrahman; Mariani Mariani (Sharia Oikonomia Law Journal, 2023)
This study is to analyze the pattern of dispute resolution in Murabahah contracts in Islamic banking. The results show that there are several commonly used dispute resolution patterns, including negotiation, mediation, and arbitration. Factors that influence the outcome of dispute resolution include trust, communication and fairness. This research provides an in-depth understanding of dispute resolution patterns in Murabahah contracts and can be a reference for Islamic banks in resolving disputes that arise. The purpose of this study is to identify and analyze the pattern of dispute resolution in Murabahah contracts in Islamic banking. This study also aims to understand the factors that influence the results of dispute resolution and provide recommendations for Islamic banking in overcoming disputes that arise. The problem to be answered in this research is how the pattern of dispute resolution in the Murabahah contract in Islamic banking. This research uses a descriptive qualitative method with an interpretative approach. Data were obtained through literature studies and document analysis related to dispute resolution in Murabahah contracts. The interpretative approach is used to understand and analyze the pattern of dispute resolution in depth, as well as the factors that influence the outcome of dispute resolution. Based on the analysis, it can be concluded that the pattern of dispute resolution in Murabahah contracts in Islamic banking includes negotiation, mediation, arbitration, and reconciliation. Factors such as trust, communication, fairness, and understanding of sharia principles influence the outcome of dispute resolution.